Tacky “Shakespeares” in Japan - Yoshihara, Yukari (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
There is no doubt that Shakespeare is “the flagship commodity” in the globalized cultural market. The fact that his works are being studied, performed, and admired, or, adapted and parodied almost all over the world, would surely testify that his works are great sources to be capitalized on (both culturally and materially) in the consumerist society in which we live. However, it could be also argued that the brand logo, “Shakespeare,” no longer holds such a privileged status, that it is merely one of numerous cultural artifacts that can be used and recycled, and that one of the few convenient things about “Shakespeare” is that it can be reproduced, copied, and parodied without the need for any royalty payments being made? Some popular, global, tacky “shakespeares” seek to destabilize the presupposed notion that “Shakespeare” is the dominant, central, hegemonic icon by juxtaposing “Shakespeare” with other artifacts, which are presumed to be of minimal capitalist and cultural value. This article attempts to illustrate how (in)significant or (un)influential Shakespeare, as a residual socio-cultural icon, can be. Tackyfying “Shakespeares” can, however, also be a means to proliferate the Bard. Japanese pop “Shakespeares,” proudly and assertively tacky, offer tributes to the great Bard.